2009
DOI: 10.1136/qshc.2008.027649
|View full text |Cite
|
Sign up to set email alerts
|

Improving colon cancer screening rates in primary care: a pilot study emphasising the role of the medical assistant

Abstract: The MA can play a key role in improving CRC screening rates as part of a redesigned system of primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…4,5,7 Outcomes in studies that have focused on or included MA role expansion or innovation have varied. Some pilot programs have found improvements in cancer screenings 4,6 , cholesterol levels 21 , diabetes control 11,21 , medication adherence 19 , physical activity levels and body mass index. 9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7 Outcomes in studies that have focused on or included MA role expansion or innovation have varied. Some pilot programs have found improvements in cancer screenings 4,6 , cholesterol levels 21 , diabetes control 11,21 , medication adherence 19 , physical activity levels and body mass index. 9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients.…”
mentioning
confidence: 99%
“…iors 2 , track lab reports 3 , identify preventive and chronic care gaps [3][4][5] , outreach to patients for cancer screenings 6 , call patients after emergency department visits or hospitalizations 3 , reconcile medications 7 , scribe clinical encounters in electronic medical records 1 , offer HIV screenings 8 , and administer vaccinations per protocol. 5 They also serve as health coaches to improve lifestyle behaviors 9 , chronic disease care processes 3,10 -18 , and medication adherence.…”
mentioning
confidence: 99%
“…These are precisely the topics most discussed in the literature (8)(9)(10)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in the context of clinical practice in primary care and its relationship to specialized care in gastroenterology. Also common were consultations on intestinal transit disorders, mainly diarrhea, as well as problems related to interpretation hepatitis virus serologies or monitoring of chronic liver disease of viral etiology and other situations of chronic hypertransaminasemia.…”
Section: Care Reasons For Consultationmentioning
confidence: 99%
“…Implementation of panel management has been linked to improvements across multiple quality measures, including rates of cancer screening, immunizations, diabetes care, cardiovascular disease care, blood pressure control, and smoking cessation counseling. [13][14][15][16][17][18][19][20] Panel management is emerging as a prominent component of transformed models of high-performing primary care 21 and is a requirement for achieving recognition as a patient-centered medical home. 22 In this environment, it is important to define and measure how clinics are achieving new care models.…”
Section: Introductionmentioning
confidence: 99%